Ответы и объяснения

2013-05-24T22:10:21+04:00

Решение во вложении

***********************************************************

  • Участник Знаний
2013-05-24T22:17:20+04:00

 

 \frac{2}{x^2+10x+25}-\frac{10}{25-x^2}=\frac{1}{x-5} 

 

\frac{2}{(x+5)^2}+\frac{10}{(x-5)(x+5)}-\frac{1}{x-5}= 0 

 

 \frac{2(x-5)+10(x+5)-1(x+5)^2}{(x+5)^2(x-5)}

 

  \frac{2x-10+10x+50-x^2-10x-25}{(x+5)^2(x-5)} 

 

  \frac{-x^2+2x+15}{(x+5)^2(x-5)} 

 

  -x^2+2x+15=0 

 

  x^2-2x-15=0 

 

  D=2^2+4*15*1=4+60=64 

 

  x1=(2+8)/2=5 

 

  x2=(2-8)/2=-3